2011
DOI: 10.11646/zootaxa.2882.1.6
|View full text |Cite
|
Sign up to set email alerts
|

The nymph of Anacroneuria debilis (Pictet, 1841) (Plecoptera: Perlidae)

Abstract: The nymph of Anacroneuria debilis (Pictet, 1841) is described, being the first immature of this genus described in Brazil. It can be distinguished from other described Anacroneuria nymphs by: (1) the presences of a row of fine, long bristles along the tibia; (2) by the absence of long bristles on the frons; (3) due to its distinctive color pattern; and (4) by the presences of rows of bristles on the basal third of the cercus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Another point found in the bibliography consulted is the general preference of the Perlidae family for streams with currents and associated with rocky substrates and with retained leaves , Bispo & Froehlich 2008, Dorvillé & Froehlich 2001, Avelino-Capistrano et al 2011a, 2015, Almeida et al, 2018, the Perlidae nymphs collected in the present study were also found in these substrates. In the case of the information obtained from the nymphs of the Gripopterygidae, mention is made mainly of areas of rocky rapids with the presence of vegetable substrate (twigs, leaf packs, epilithic vegetation), low water level and laminar flow in the case of the genus Gripopteryx , similar areas are also described for the genus Paragripopteryx, but areas with the presence of bryophytes and algae or in cavities or crevices of stones are also mentioned ).…”
Section: Discussionsupporting
confidence: 57%
“…Another point found in the bibliography consulted is the general preference of the Perlidae family for streams with currents and associated with rocky substrates and with retained leaves , Bispo & Froehlich 2008, Dorvillé & Froehlich 2001, Avelino-Capistrano et al 2011a, 2015, Almeida et al, 2018, the Perlidae nymphs collected in the present study were also found in these substrates. In the case of the information obtained from the nymphs of the Gripopterygidae, mention is made mainly of areas of rocky rapids with the presence of vegetable substrate (twigs, leaf packs, epilithic vegetation), low water level and laminar flow in the case of the genus Gripopteryx , similar areas are also described for the genus Paragripopteryx, but areas with the presence of bryophytes and algae or in cavities or crevices of stones are also mentioned ).…”
Section: Discussionsupporting
confidence: 57%
“…Currently, the nymphs of only 23 species of Anacroneuria are known. In Brazil, only nine of 150 species are known as nymphs (Righi-Cavallaro & Lecci 2010, Silva et al 2011Novaes et al 2012). In the present study nymphs of three species of the genus Anacroneuria from the Brazilian Amazon are associated with adults for the first time and compared.…”
Section: Introductionmentioning
confidence: 83%